2006
DOI: 10.4028/www.scientific.net/ast.49.124
|View full text |Cite
|
Sign up to set email alerts
|

Reinforcement of Denture Base Resin

Abstract: The fracture resistance of polymethyl methacrylate (PMMA) the most popular denture base materials, is not satisfactory. The aim of this study is to improve the mechanical properties of PMMA by adding filler particles. Different inorganic filler particles including micronised glass flakes, acryl silane micronised, glass flakes 350nm, TiO2 and ZrO2 with different ratios by weight were incorporated into heat-cure plain PMMA and processed with optimal condition [2.5:1 Powder/ monomer ratio, conventional packing me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
42
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 27 publications
(28 reference statements)
3
42
0
Order By: Relevance
“…1,2 However, PMMA has poor mechanical properties, which often results in denture base fractures. 3 Such denture fractures may occur inside the patient's mouth usually at the midline of the denture base during mastication or outside the patient's mouth when the removable prosthesis drops suddenly.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 However, PMMA has poor mechanical properties, which often results in denture base fractures. 3 Such denture fractures may occur inside the patient's mouth usually at the midline of the denture base during mastication or outside the patient's mouth when the removable prosthesis drops suddenly.…”
Section: Introductionmentioning
confidence: 99%
“…56 Titanium (TiO 2 ) Several studies have investigated the effect of adding titanium dioxide (TiO 2 ) on the properties of PMMA. It was found that adding TiO 2 particles could improve the flexure strength, fracture toughness, hardness of PMMA, 26,40,57,58 as well as thermal conductivity. 33 In addition, a significant increase in impact strength 59 and a significant decrease in water sorption and solubility were found upon addition of TiO 2 to PMMA.…”
mentioning
confidence: 99%
“…The soft liner provides comfort for the patient and may reduce residual ridge resorption by reducing impact force in the loadbearing areas in the supporting structures during function [4] . Polymethyl methacrylate (PMMA) resins have been the most popular denture base resins because of their physical and esthetic properties, accurate fit, stability in oral environment as well as the material's availability, reasonable cost, and ease of manipulation [5,6] .…”
Section: Introductionmentioning
confidence: 99%